2007
DOI: 10.1111/j.1442-9071.2007.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Contemporaryin vivoconfocal microscopy of the living human cornea using white light and laser scanning techniques: a major review

Abstract: In vivo confocal imaging of the cornea has evolved exponentially over the last few decades and it has increasingly emerged from the laboratory to be used in the clinical setting in relation to inherited corneal diseases, corneal infections, contact lens wear and the effects of corneal surgery. This evolution has led to significant enhancement of our knowledge of the living cornea in both its physiological and pathological states. A number of in vivo confocal microscope devices using white, and more recently co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(151 citation statements)
references
References 110 publications
(340 reference statements)
4
145
1
1
Order By: Relevance
“…24 The enhanced image brightness and contrast of LSCM allows a qualitative evaluation of certain subtle features of the cornea. 25 Kobayashi et al 26 first reported the presence of microstructures (called K-structures) observed at the level of Bowman's layer in normal subjects with the aid of LSCM, which were not evident with slit scanning confocal microscopy, suggesting that LSCM offers considerably higher image quality compared with conventional white-light confocal microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…24 The enhanced image brightness and contrast of LSCM allows a qualitative evaluation of certain subtle features of the cornea. 25 Kobayashi et al 26 first reported the presence of microstructures (called K-structures) observed at the level of Bowman's layer in normal subjects with the aid of LSCM, which were not evident with slit scanning confocal microscopy, suggesting that LSCM offers considerably higher image quality compared with conventional white-light confocal microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, the evaluation of KP with IVCM has been limited; the literature contains one report by Wertheim et al 2 in 2004 of findings in 33 patients with different forms of uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, confocal microscopy can serve as a valuable tool for live cell imaging. Clinically, CLSM is used in the evaluation of various eye diseases, and is particularly useful for imaging, qualitative analysis, and quantification of endothelial cells of the cornea (Patel and McGhee, 2007). It is used for localizing and identifying the presence of filamentary fungal elements in the corneal stroma in cases of keratomycosis, enabling rapid diagnosis and thereby early institution of definitive therapy.…”
Section: Living Cells Imagingmentioning
confidence: 99%